'Modern' Phillips curves and the implications for the statistical process of inflation. Issue 1 (2nd January 2017) - Russell, Bill
ABSTRACT: 'Modern' theories of the Phillips curve imply that inflation is an integrated, or near integrated' process. This article explains this implication and why these 'modern' theories are logically inconsistent with what is commonly known about the statistical process of inflation.